An integration data of e-SKT and lecturer promotion in FSKM / Azuani Mat Sudin - Mat Sudin, Azuani (2010)
This project describes about of integration between two data sources of e-SKT (Sasaran Kerja Tahunan) and Lecturer Promotion. The aim for this project is to develop an integration design for e-SKT system according lecturer promotion. There are three main focuses. The first stage is discovered about investigate the technique and process of data integration from two different sources which is from the E-SKT system and the excel spreadsheet (lecturer promotion). The next phase is to design the integration of data model of e-SKT to excel for lecturer promotion and the third part is to demonstrate the integration function data. In addition, data federation approaches has been use to cover on the technique of integration. The detail requirements have been documented in Software Requirement Specification (SRS) and Software Detailed Design (SDD).